An Assessment of the Three Popular Prognostic Scoring Systems for Chronic Myelomonocytic Leukemia (CMML) in an Indian Context - Saha, Anurag; Kakoty, Sneha; Patel, Kazoomi; Rai, Varnika; Sawhney, Jyoti; Menat, Nainesh (Indian Journal of Medical and Paediatric Oncology, 2023)
Introduction: Chronic myelomonocytic leukemia (CMML) is a rare clonal hematopoietic neoplasm with a prevalence of 1.05 to 1.94 cases per 1,00,000 population. There are multiple prognostic scoring system used in practice for CMML, which include both cytogenetic and next-generation sequencing based.Objective This study assesses the clinicohematological profile of CMML patients, along with comparison of three widely used prognostic scoring systems for CMML (CMML-specific prognostic scoring system, MD Anderson prognostic score, Mayo prognostic model).Materials and Methods: This study is an 8-year retrospective study. All relevant data had been retrieved and reviewed by the authors. Inclusion and exclusion criteria: All the cases that were diagnosed before 2016 as per 2008 criteria were reclassified, (2) all the cases that were positive for the mutations associated with myeloproliferative neoplasms were excluded, and (3) cases with more than or equal to 20% blast/blast equivalents were excluded. A univariate analysis was done followed by a multivariate analysis for all the parameters constituting each scoring system. Lastly, a receiver operating characteristic curve was plotted for all the three scoring systems.Result: There were total 23 patients, with a median age of 63 years and a male to female ratio of 2.3:1. Cytogenetic aberration and genetic mutation were observed in 6 and 3 cases, respectively. The median overall survival (OS) was 48 months and the median leukemia-free survival was 12 months. Post-multivariate analysis, the parameters with significant impact on OS were absolute monocyte count more than 10 × 10^9/L, myeloid precursors in peripheral blood, hemoglobin less than 10g/dL, platelet less than 100 × 10^9/L, hemoglobin less than 12g/dL, and absolute lymphocyte count more than 2.5 × 10^9/L.Conclusion: To summarize, we discovered CPSS to be a better prognostic tool for a setup like ours, since molecular investigations are not always readily available for each case. More such researches are needed in the near future so that we can design better prognostic tools and see for their usefulness in real life.
Keywords: CMML; prognostic tools; cytogenetics; overall survival; leukemia-free survival.